NURSE’S AUTONOMY IN THE DELEVERY OF NORMAL BIRTHS IN BRAZIL - Barros, Lena María; Magalhães da Silva, Raimunda; Rejane Moura, Escolástica Ferreira (Investigación y Educación en Enfermería, 2008)
Objective: To identify factors which interfere on nurse’s autonomy in normal delivery assistance. Methodology: Qualitative and exploratory study, carried through with 9 nurses of 4 obstetric center of public maternities in São Luis, Maranhão, Brazil, from April to May of 2002, through recorded interview. Results: Nurse’s autonomy in normal delivery assistance is influenced by physician’s power and nurse’s submission, by the lack of acquaintance to legal support which assures to the nurse to perform this care taking matter, by the weak technical-scientific knowledge to deal with deliveries and by daily work activism, which motivate a recall of dependence and professional lack of confidence. Conclusion: It is necessary that this category has itself mobilized and gather efforts to raise its autonomy basis, primarily supported by competence and determination of roles.